EFEKTIFITAS PENGELOLAAN LIMBAH CAIR PADA INDUSTRI KAYU LAPIS DI KALIMANTAN SELATAN - D. Subari; Udiansyah Udiansyah; B. Yanuwiyadi; B. Setiawan (Universitas Tribhuwana Tunggadewi, 2012)
This paper reports the effectiveness and efficiency of wastewater treatment decreased levels of contamination in the treatment of wastewater from three plywood industries in in South Kalimantan. The results showed that the liquid waste from washing mixer glue and glue spreader quality was lower than the quality of streams Barito’s river and Martapura’s river, so if not treated will cause pollution in the river flows. Results of waste analyses at the inlet and outlet showed that the efficiency of WWTP in the plywood industry was high at 67% to 99%, with 0.007 m3/m3 water discharge of the product. Based on South Kalimantan Governor Decree No. 036 of 2008, the maximum discharge of 0.30 m3/m3 of products, so as to meet quality standards. Sludge at the WWTP can be used as a mixture of adhesive (filler)